FAKTOR â FAKTOR YANG MEMPENGARUHI KUALITAS AUDIT - Dwimilten, Eunike; Riduwan, Akhmad (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to find out the influence of competency, independency, accountability, time budget pressure and due professional care to the audit quality. The respondents are auditor staffs from junior to manager position who works at Public Accountant Office in Surabaya and Sidoarjo. The samples are 14 Public Accountant Offices which are represented by 70 people of auditor staffs, who have been selected by using simple random sampling method. The data has been obtained by issuing questionnaires which are directly issued to the respondents in the beginning of April 2015. The multiple linear regressions are used as the analysis technique. The results of the research have proven that i.e.: (a) the competency has positive influence to the audit quality, it means that the qualified audit is obtained from the high competency of auditors; (b) the independency has positive influence to the audit quality, it means that when the independency of an auditors is better, the audit quality is better as well; (c) accountability has positive influence to the audit quality, it means that when the auditors have high responsibility on their jobs, it will generate high audit quality; (d) time budget pressure has positive influence to the audit quality, it means that the time budget can encourage the auditors to maximize the existing time and to generate qualified audit; (e) due profesionalcare has positive influence to the audit quality, it means that when the careful and thoroughly professionalism of an auditor is high, the audit quality is high as well.Keywords: Competency, Independency, Accountability, Time Budget Pressure, Due Professional Care, Audit Quality.